Sulfone-modified chitosan as selective adsorbent for the extraction of toxic Hg(II) metal ions - Youssef O Al-Ghamdi; Khalid A Alamry; Mahmoud A Hussein; Hadi M Marwani; Abdullah M Asiri (Adsorption Science & Technology)
In this study, a new category of sulfone-modified chitosan derivatives as surface-selective adsorbents for the extraction of toxic Hg(II) metal has been synthesized in good yield. Sulfone-modified chitosan/5–20 based on variable loading of the corresponding phenacyl bromide (5, 10, 15, and 20% with respect to the original weight of the pure chitosan) was synthesized. The β-ketosulfone derivative, namely 1–(4-bromophenyl)-2-(phenylsulfonyl)ethanone, was first prepared by treatment of the corresponding phenacyl bromide with a sufficient amount of sodium benzene sulfinate; its chemical structure was confirmed by spectral analyses, including Fourier transform infrared spectroscopy, 1 H-NMR, 13 C-NMR, and mass spectrometry. Then, sulfone-modified chitosan/5–20 derivatives were synthesized by the interaction of chitosan with a freshly prepared p-bromo-β-ketosulfone derivative in a mildly acidic aqueous solution using the solution-blending technique. Sulfone-modified chitosan/5–20 derivatives were identified and characterized using common characterization techniques, including Fourier transform infrared spectroscopy, ﬁeld-emission scanning electron microscope, powder X-ray diffraction, and thermal behaviour. A strong interaction was displayed between chitosan and its corresponding β-ketosulfones in powder X-ray diffraction, which was confirmed by significant 2θ shifts. Sulfone-modified chitosan/5–20 derivatives were detected as catalysts, which efficiently increased the thermal decomposition of pure chitosan. More particularly, the efficiency of sulfone-modified chitosan/5–20 derivatives for Hg(II), Pb(II), Ni(II), Al(III), Sr(II), Cr(III), Fe(III), Zn(II), and Mn(II) detection and adsorption was also investigated using inductively coupled plasma optical emission spectrometry. The sulfone-modified chitosan/5 derivative exhibited the highest adsorption efficiency. The most effective quantitative adsorption onto the sulfone-modified chitosan/5 surface was detected at pH = 2. In addition to that, the adsorption isotherm showed that the adsorption capacity of sulfone-modified chitosan/5 for Hg(II) was 122.47 mg g −1 and that its adsorption isotherm was in agreement with the Langmuir adsorption isotherm.